A Study on the φ-Symmetric K-Contact Manifold Admitting Quarter-Symmetric Metric Connection - Bagewadi, C.S.; Ingalahalli, G. (Журнал математической физики, анализа, геометрии, 2014)
The local φ-symmetry and φ-symmetry of a K-contact manifold with respect to the quarter-symmetric metric connection are studied and the results concerning the φ-symmetry, scalar curvature with respect to the quarter- symmetric and the Levi-Civita connection are obtained. Further, the locally C-Bochner φ-symmetric and the locally φ-symmetric K-contact manifolds with respect to the quarter-symmetric metric connection are studied and some results are obtained. The results are assisted by the examples. Изучены локальная φ-симметричность и φ-симметричность К-контактного многообразия относительно четверть-симметрической метрической связности и получены результаты, касающиеся φ-симметрии, скалярной кривизны по отношению к четверть-симметрической связности и связности Леви-Чивита. Кроме того, изучены локально C-бохнеровские φ-симметрические и локально φ-симметрические K-контактные многообразия по отношению к четверть-симметрической метрической связности и получены некоторые результаты. Результаты подкреплены примерами.